ASSESSMENT OF AMBIENT AIR QUALITY IN THE SURROUNDING AREA OF COMPOST PLANT, DELHI, INDIA - Prakash, Mamta; Mandal, Papiya; Chaturvedi, M. K.; Srivastava, Anjali (Malaysian Journal of Science, 2017)
A short-term study was conducted with a view to assess the ambient air quality in the surroundings area of compost plant at Okhla, Delhi. Three selected locations viz., CRRI Campus, Hazi Colony, and Gaffar Manzil were selected during the month of November 2008. The study revealed that 24 hourly average concentration of respirable suspended particulate matter (RSPM) at all selected locations were alarmingly high as compared to National Ambient Air Quality Standards (NAAQS) specified by Central Pollution Control Board (CPCB) 2009, during the study period. The 24 hourly average concentrations of sulphur dioxide (SO2) and ammonia (NH3) were within the permissible limits prescribed by the NAAQS. Nitrogen dioxide (NO2) concentration was found to exceed the permissible limits at all the three locations with percent exceedence ranging between 67%-75%. High concentrations of NO2 could be due to auto-exhaust emissions on Delhi- Mathura road, burning of LPG gas for domestic use, incinerator stack gases and diesel run electric generator. The concentrations of H2S were low, which could be due to aerobic nature of waste processing composting plant. The 8 hourly average concentration of CO was quite high at all the three monitoring stations. Percent exceedence of CO levels ranged between 83% - 86%. The localized domestic and automobile emissions in surrounding areas could be the major contributor of CO. The overall assessment of the air quality during the study period at selected locations indicated that the maximum contribution of pollutant responsible for critical Air Quality Index (AQI) values was the respirable particulate matter (RSPM) which fell under the category of severe on majority of the days. Keywords: Compost Plant, Air Pollutants, Air Quality Index (AQI)